Roots and Shoots: Building Bridges between Schools and Their Communities - Jan Cincera (MDPI AG, 2021)
The study analyses the benefits and challenges emerging from students’ interactions with community, teachers, and other students in the place-based education program Roots and Shoots, in the Slovak Republic. The study is based on qualitative analyses of data obtained from eight teachers and 56 students interviewed in eight focus groups, and on quantitative data obtained from 53 students. Both the students and the teachers perceived the Roots and Shoots program as highly successful. The implementation of the program was challenged by the necessity of dealing with different levels of the students’ participation in decision-making, tensions between the involved and uninvolved students, and the complex nature of local sustainability issues. This study discusses the importance of engaging students in the participative process of solving real-world issues, reflecting the challenges of this educational approach.